2023
DOI: 10.1097/aco.0000000000001321
|View full text |Cite
|
Sign up to set email alerts
|

The high-risk pediatric patient for ambulatory surgery

Audra M. Webber,
Marjorie Brennan

Abstract: Purpose of review The aim of this article is to briefly review the pediatric ambulatory surgery landscape, identify two of the most common comorbidities affecting this population, examine the influence of pediatric obesity and sleep disordered breathing (SDB)/obstructive sleep apnea (OSA) on perioperative care, and provide information that can be used when formulating site specific criteria for ambulatory surgical centers. Recent findings Most pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This recommendation conflicts with the current medical concern of reducing prolonged or unnecessary anesthesia exposure in children younger than 3 years, due to the high correlation with neurodevelopmental side effects 7–9 . In a recent study published by Webber and Brennan, the use of anesthesia among the pediatric population had a higher degree of procedural complications 10 . Based on this belief, recent studies have identified several risk factors that could predict the presence of underlying MRI pathology in patients with Congenital-EOS 11 .…”
mentioning
confidence: 99%
“…This recommendation conflicts with the current medical concern of reducing prolonged or unnecessary anesthesia exposure in children younger than 3 years, due to the high correlation with neurodevelopmental side effects 7–9 . In a recent study published by Webber and Brennan, the use of anesthesia among the pediatric population had a higher degree of procedural complications 10 . Based on this belief, recent studies have identified several risk factors that could predict the presence of underlying MRI pathology in patients with Congenital-EOS 11 .…”
mentioning
confidence: 99%